Performance analysis of an S‐band antenna for nanosatellite payloads communication system. Issue 11 (16th October 2018) - Alam, Touhidul; Islam, Mohammad Tariqul; Amanath Ullah, Md.; Cho, Mengu
Abstract: The nanosatellite concept was born from the low‐cost small satellite educational research activities that lead to the nanosatellite revolution. However, in recent years, the development of the nanosatellite is not for just research purpose but commercial opportunities as well. Antenna is very crucial part of the nanosatellite communication system that establishes communication between space to ground. In this paper, an S‐band circular polarized (CP) antenna is presented and investigate the performance compatibility for nanosatellite space mission. The antenna was fabricated on 1.575 mm thick Rogers 5880 substrate material. The measured result shows that the antenna has a −10 dB reflection coefficient bandwidth of 1.64%, 3 dB axial‐ratio bandwidths of 38 MHz and realized gain of around 5.58 dB at the resonant frequency. The antenna was integrated with 2 U nanosatellite structure and investigated the antenna performance.